Assessment of Thermodynamic and Structural Properties of Al–Er liquid Alloy at Different Temperatures (The Journal of Knowledge and Innovation, 2023)
Theoretical expressions of quasi–lattice model were used to assess the thermodynamic and structural properties of Al–Er liquid alloy at different temperatures. The model fit parameters were optimised using the available literature data of the thermodynamic properties for the system at 1873 K. The computed values of thermodynamic properties such as excess Gibbs free energy of mixing, enthalpy of mixing, entropy of mixing and activities of Er and Al using the model fit parameters were found to be consistent with the reference data–set. Therefore, the same parameters were used to compute the structural properties such as concentration fluctuation in long wavelength limit, Warren–Cowley short range–order parameter and ratio of mutual to intrinsic diffusion coefficients. Assuming the model fit parameters to be linear temperature–dependent, the above mentioned properties were also assessed in the temperature range 1873–2173 K. The compound forming tendency of the system was found to decrease gradually with increase in temperature.